Relativization in Ojibwe - Sullivan, Michael D., Sr (Book collections on Project MUSE., 2020)
"Following previous dialect studies concerned primarily with varieties of Ojibwe spoken in Canada, Relativization in Ojibwe presents the first study of dialect variation for varieties spoken in the United States and along the border region of Ontario and Minnesota"--